A detailed survey for determination of the grafted semifluorinated acrylic compound effect on thermal, microstructural, free volume, mechanical and morphological features of HDPE - TAV, CUMALİ; YAHŞİ, UĞUR (ELSEVIER SCIENCE SA, 2020)
This study mainly aims to investigate the role of grafted semifluorinated acrylic compound in the crucial characteristic properties of high density polyethylene (HDPE). Graft copolymerization of the semifluorinated acrylic compound, 3,3,4,4,5,5,6,6,7,7,8,8,8-dodecafluoro-5-methyloctyl-4-(acryloyloxy) benzoate (ABCF13) onto HDPE within the different content levels of ABCF13 (5, 10, 15, 20, 30 and 40 %) was performed by bulk-melt polymerization method. The changes in the thermal, microstructural and free volume characteristics of graft coproducts with extent of grafting were investigated in detail by means of DSC, powder X-ray diffraction and PALS techniques, respectively. The experimental findings showed that the melting temperature of crystalline domains and crystallinity ofHDPE reached the maxima at the 15 % and 40 % ABCF13 contents, respectively. The grafting of ABCF13 onto HDPE also gave rise to significant expansion and contraction in lateral dimensions of orthorhombic unit cell parameters in the crystalline domains of HDPE. Moreover, PALS analyses depicted that the size of the free volumes increased almost linearly with the grafting percentage. As for mechanical behaviours of the graft products, remarkable improvements were achieved in especially tensile strength (from 18.75 MPa to 43.75 MPa) and impact strength (from 19.30 Mpa to 38.72 MPa). The morphological properties of the fractured surfaces obtained from tensile and impact tests of products were also examined by SEM analysis. The samples possessed completely homogeneous structure without any phase separation. A gradual transition from ductile behaviour to brittle nature was observed as the grafting level increased in the products.
Keywords: High density polyethylene; Semi-fluorinated acrylic compound; Grafting; Mechanical reinforcement; Unit cell parameters; Free volume; LIQUID-CRYSTALLINE POLYMER; POSITRON-ANNIHILATION; METHYL-METHACRYLATE; BLENDS; POLYETHYLENE; COMPATIBILIZATION; POLYPROPYLENE; COPOLYMERS; POLYCARBONATE; TEMPERATURE